Utilização da metaheurística Simulated Annealing no problema de alocação de pessoal em empresas de transporte coletivo por ônibus - Gomes, Heider Augusto da Silva (2003)
Crew scheduling is an important stage ofthe operational planning of transit. The expenses with drivers and collectors represent a considerable part of the bus companies costs, with direct effects on the values of the fares. Those costs, the economic situation of the country and the new regulation modelsare generating actions to improve vehicle and crew scheduling procedures. The purpose ofthe present research is to develop a new software tool to be used for bus crewscheduling. The methodology to be used will consider the application of metaheuristic Simulated Annealing, with which it is intended to produce a set of solutions, allowing the decision maker to selectone based on his/her experience that will give a better overcoming. The software tool has presented quite satisfactory results for some tested lines implying in a reduction in the costs adopted by the company operator of that type of transport system. However, it was verified that they are still necessary some agreement. This way, the softwaretool becomes more robust and more efficient. That is due to the fact that the software tool doesn't consider some peculiarities that they are adopted by the companies, but that can be accomplished, if necessary, starting from manual alterations in the final solution supplied by the program.